Kontribusi Ibu Rumah Tangga yang Berpendidikan Tinggi dalam Memberikan Pendidikan Religiusitas Anak - Suhirman Suhirman; Azwar Rahmat; Yesi Purwaningatmaja (Jurnal Hawa : Studi Pengarus Utamaan Gender dan Anak, 2022)
Data collection techniques used were observation, The purpose of this study was to determine the contribution of housewives who have higher education in providing children's religious education in Fajar Baru Village, Ketahun District, North Bengkulu. This “research is a quantitative questionnaires, and documentation. For sampling techniques used purposive sampling techniques, and data analysis” techniques using the mean, standard deviation, and product moment formula to find the relationship. The results obtained from this study are there are contributions between highly educated housewives on children's religious education in Fajar Baru Village, Ketahun District, North Bengkulu. This can be proven from the statistical calculation that r is greater than rtable (-0.236 <0.284) ts 5%, there is a significant contribution among housewives with high education towards children's religiosity education. This can be seen from the majority of housewives with minimum education qualifications of junior high, high school, and highest level 1 (undergraduate). Then the children's religious education in Fajar Baru Village is also in the medium category. This shows the child has gradually implemented religious teachings in everyday life. Such as, believing in the oneness of Allah, believing mace and qadar, being polite to teachers, parents, and others, performing compulsory prayer and circumcision, fasting in the month of Ramadan, and having a noble character.